Analysis of Poetic Arts in the Creation of Abdullo Sher - Sayyora Khaqnazarova; Umrzokhova Gulzoda (Journal of Research in Innovative Teaching and Inclusive Learning, 2023)
This article talks about the poetic work of Abdulla Sher, a poet and translator. The poet's creative style, various forms used in poetry are revealed.